Keberkahan Al-Aqsha Perspektif Hermeneutika Schleiermacher - Abdul Fatah (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
In Surah al-Isra (17) verse 1 al-Qur'an mentions clearly that around al-Aqsa has been blessed by Allah SWT. But historically it has been proven that in Jerusalem, the palce where al-Aqsa is exist became a cause of conflict between divine religions that led to the death of thousands innocent, so where were the blessing of al-Aqsa?To answer this question researchers used a hermeneutic approach of Schleiermacher namely grammatical and psychological interpretations that are considered able to observe and photograph the Surah al-Isra (17) verse 1 with the empirical reality today in Jerusalem. The result of this study as follows: the blessing in Surah al-Isra verse 1 which is the characteristic of al-Aqsa Mosque is a depiction of holiness the transfer through a procession of Isra Mi'raj of Prophet Muhammad in the form of journey safety so that there is no interruption in his journey. The existence of the blessing in surah al-Isra (17) verse 1 is more specific and personal to the prophet Muhammad when conducted night journey from al-haram mosqueto al-Aqsa mosque